2016
DOI: 10.1080/02626667.2015.1052454
|View full text |Cite
|
Sign up to set email alerts
|

Differences in throughfall drop size distributions in the presence and absence of foliage

Abstract: Throughfall drop size distributions (DSDs) are important for plant-soil interactions. This is the first known study to quantify differences in throughfall DSDs with the presence and absence of foliage. Employing a disdrometer, three parameters solely representing throughfall drip were measured and calculated: maximum drop diameter (D MAX ), median volume diameter of drops (D 50 D R ), and relative volume percentage of drops (pD R ). Beneath Liriodendron tulipifera L. in Maryland (USA), D MAX , D 50 D R , and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 39 publications
2
54
0
3
Order By: Relevance
“…With regard to throughfall drop‐size distributions, Nanko et al () and Nanko, Watanabe, Hotta, and Suzuki () found that throughfall drop‐size distributions differed among tree species due to variable plant surface characteristics. Throughfall drop diameters have been found to be larger beneath a leafless broadleaved tree than a leafed one when a structurally created branch drip point is amplified by the absence of foliage (Nanko, Hudson, & Levia, ). Building on these earlier studies, this work seeks to better understand the relative proportions of throughfall types within forests as well as how throughfall type varies beneath foliar and woody surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to throughfall drop‐size distributions, Nanko et al () and Nanko, Watanabe, Hotta, and Suzuki () found that throughfall drop‐size distributions differed among tree species due to variable plant surface characteristics. Throughfall drop diameters have been found to be larger beneath a leafless broadleaved tree than a leafed one when a structurally created branch drip point is amplified by the absence of foliage (Nanko, Hudson, & Levia, ). Building on these earlier studies, this work seeks to better understand the relative proportions of throughfall types within forests as well as how throughfall type varies beneath foliar and woody surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For each event, the number of drops, their diameter, and their velocity were obtained from the disdrometer's raw data. The event's median volume diameter (D50) [6], rainfall kinetic energy [32,33], and the number of raindrops per event were calculated according to disdrometer's measuring area (54 cm 2 ). The velocity spectrum is largely redundant with the size spectrum, as drop terminal velocity depends on its size (v = v(D)).…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Throughfall splash droplets are usually smaller than drops induced by dripping. Most often, a throughfall drop diameter of 1.5 mm has been measured as the threshold value determining a specific throughfall component, as smaller drops are splash-induced and larger drops are generated by dripping [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall reaches the forest floor via TF and SF. International researchers have conducted a number of studies on these processes 913 . Primary forest types include coniferous forests, Chinese firs, Q. monimotricha forests, temperate deciduous forests, larch forests, tropical rain forests and subtropical evergreen forests 14–18 .…”
Section: Introductionmentioning
confidence: 99%